2017
DOI: 10.3390/socsci6010018
|View full text |Cite
|
Sign up to set email alerts
|

Receiving Assistance and Local Food System Participation

Abstract: A body of literature has noted that local food systems (LFSs) may not involve active participation by individuals with lower incomes. This is, in part, a function of racial and class hegemony, as well as physical and financial accessibility of LFSs. LFS institutions, such as farmers' markets, have been working to facilitate receipt of food assistance programs, such as the Supplemental Nutrition Assistance Program (SNAP). Charitable assistance programs, such as food banks, have also been actively working to eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, intentions to start a new entrepreneurial activity are also affected by the pursuit of economic profits (Giacomin et al ., 2011). Finally, in her study, Som Castellano (2017) found that farmers' environmental concern is associated with the possibility of participating in alternative food distribution schemes. Hence, we also examined the influence of farmers' citizenship behavior, their perception of the potential economic benefits from participation, and their environmental concern on their willingness to engage in SFSCs.…”
Section: The Present Studiesmentioning
confidence: 94%
“…In addition, intentions to start a new entrepreneurial activity are also affected by the pursuit of economic profits (Giacomin et al ., 2011). Finally, in her study, Som Castellano (2017) found that farmers' environmental concern is associated with the possibility of participating in alternative food distribution schemes. Hence, we also examined the influence of farmers' citizenship behavior, their perception of the potential economic benefits from participation, and their environmental concern on their willingness to engage in SFSCs.…”
Section: The Present Studiesmentioning
confidence: 94%
“…22,38,39 An individualized approach needs to be considered when delivering SNAP to family with different social economic conditions, for example, focusing on assistance in making supplemental food available locally. 40…”
Section: Caregivers' Perceptions That the Children Are Not In Fact mentioning
confidence: 99%